116 Ct coronary angiography versus coronary artery calcium scoring for the occupational assessment of military aircrew. (5th June 2017) - Parsons, Iain; Pavitt, Christopher; Chamley, Rebecca; D'Arcy, Jo; Nicol, Ed
Abstract : Introduction: To ensure flight safety military aircrew undergo regular clinical and occupational assessment. Coronary artery calcium scoring (CACS) is established as an imaging modality to non-invasively assess coronary artery disease (CAD). CT coronary angiography (CTCA) potentially offers a more accurate assessment of CAD but has not been formally assessed in military aircrew. This retrospective cohort study is designed to compare the theoretical differences in downstream investigations and occupational outcomes in aircrew with suspected CAD comparing CTCA with existing CACS pathways. Methods: A 2 year retrospective cohort study of consecutive UK military patients who underwent a CTCA and CACS. Patient demographics, CTCA and CACS results and initial and final occupational restrictions were analysed comparing current UK, Canadian and US pathways. Results: 44 patients underwent CACS and CTCA. The commonest indication for a CTCA was a positive exercise ECG. Increasing CACS, stenosis severity and stenosis burden were associated with significantly greater likelihood of occupational restriction (p=<0.01). Following CTCA (26/44, 59%) of patients were found to have evidence of CAD with (13/44, 30%) having at least a single vessel stenosis 50%. All of these patients had subsequent occupational restrictions. Two patients with a calcium score 10 had at least one single vessel stenosis 50%. Conclusion: A CTCA pathway is potentially a better discriminator of CAD burden in aircrew when compared with CACS and may reduce downstream testing, allowing a more efficacious approach to CAD assessment in military aircrew.